Performance of high-content waste ash geopolymer-based composites for sustainable construction - Mohd Nasir, Noor Azline; Nadarajah, Archanaah; Megat Johari, Megat-Usamah; Abu Bakar, Nabilah; Safiee, Nor Azizi; Abdul Aziz, Farah N. A. (Springer Science and Business Media Deutschland GmbH, 2025)
In reference to the alumino-silicious binder materials, it is observed that almost all studies composed of binary and ternary geopolymer systems have focused on fly ash (FA) and ground granulated blast-furnace slag (GGBS) as primary source materials. Despite their technical benefits, this scenario is attributable to the high availability of the binder globally and its low cost. Various research had been done on the elimination of heat curing on the application of FA-based geopolymer composites. However, most studies have put a focus on Class-C FA, which has a high calcium content. As such, this research is exploring the enhancement of Class-F FA (low calcium content) and the potential of palm oil fuel ash (POFA) as the source of binder in FA-based geopolymer systems. POFA has similar characteristics to FA but POFA possesses slightly higher calcium content compared to Class-F FA. A systematic evaluation was carried out on an FA-based geopolymer mixture with the incorporation of GGBS. POFA was included as a secondary compound and for the tertiary compound at a range of 10%–30%. Meanwhile, 10% metakaolin (MK) was used as a tertiary compound in the FA/POFA geopolymer system. Alkaline activators of combination between sodium silicate and sodium hydroxide with a ratio of 2.5, 12 M sodium hydroxide and a liquid-to-binder ratio of 0.43 were used for the study. The geopolymerisation reactivity, setting time, flowability, and strength were the properties evaluated. Additionally, statistical analysis and sustainable assessment were done to highlight the environmental advantages. This approach offers a pathway to reduce reliance on Portland cement, contributing to environmentally friendly construction practices. Overall, the findings revealed that high FA content results in high early strength with the incorporation of GGBS. POFA demonstrates its viability for use in both FA/GGBS and FA/POFA geopolymer systems. Nonetheless, the usage of POFA should not exceed 20% when the FA content is high. FA-based geopolymer reduced carbon emissions around 68% compared to conventional cement. Ultimately, the strength achieved by the FA-based geopolymer system shows its potential as an alternative construction material for industry.